PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI DALAM PEMBELAJARAN LURING - Yantantri, Meyvita; Abubakar, Akhmad H. (STKIP Persada Khatulistiwa Sintang, 2023)
Success in the learning process is measured by student independence, student learning outcomes, and subject-matter knowledge. When a learner has a high level of subject matter mastery and learning independence, he or she will produce learning outcomes that are of a high caliber. This study attempts to determine how learning independence variables affect the cognitive, affective, and psychomotor outcomes of economics learning in high school students. Utilizing an associative research design, the research approach is quantitative. Purposive sampling was utilized for the sample. Validity and realisability tests are used to evaluate instruments. The Residuals vs. Graphics test applied to a straightforward linear test. It can be concluded that a basic linear regression test has a linear and homogeneous group variance data distribution if the predicted generated charts are randomly scattered and unaltered. The test-t resulted in thitung 23.243 > t-table 1.625 at a = 0,05, indicating that learning outcomes (cognitive, emotional, and psychomotor) for economics topics had a substantial impact on attracting learning inÂ High School students.